Antibodies against Entamoeba histolytica in individuals with intestinal amoebiasis presenting cysts and/or trophozoites in the feces - Carvalho, Maria Das Graças; Guimarães, Semíramis [UNESP]; Silva, Edward Felix (Instituto de Medicina Tropical, 1991)
Serum samples were obtained from 154 individuals infected with Entamoeba histolytica (78 symptomatic and 76 asymptomatic). Twelve had trophozoites in the feces whereas 142 had only cysts. The sera were used to test the existence of antibodies anti-Entamoeba histolytica employing the Indirect Hemagglutination (IHA), Indirect Immunofluoresccnce (IFAT), Complement Fixation Reaction (CFR) and Counterimmunoelectrophoresis (CIEP). For those individuals with trophozoites in their feces, 75.0 were positive by IHA and IFAT, 83.0 by CFR and 41.7 by CIEP. In individuals who had only cysts, positive results by the same tests were respectively, 5.6%, 12.0%, 19.0% and 5.6%. The difference in relation to the tilers of antibodies detected through IHA, IFAT, CFR and CIEP and in relation to the presence of trophozoites or cysts in the feces was significative for four immunological reactions when X², was employed (P < 0.05).

Amostras de soros foram obtidas de 154 indivíduos comprovadamente parasitados pela Entamoeba histolytica (78 sintomáticos c 76 assintomáticos). Doze apresentavam trofozoitas nas fezes, enquanto 142 tinham apenas cistos. Os soros foram utilizados para testar a ocorrência de anticorpos anti-Entamoeba histolytica, empregando-se para tal, Reação de Hemaglutinação Indireta (HAI), Reação de Imunofluorescência Indireta (RIFI), Reação de Fixação de Complemento (RFC) e Contraimunoeletroforese (CIEP). Entre os soros dos indivíduos com trofozoitas em suas fezes, 75,0% foram positivos para HAI e RIFI, 83,3% por RFC, e 41,7% por CIEP. Nos indivíduos que tinham apenas cistos, resultados positivos pelos mesmos testes foram respectivamente, 5,6%; 12,0%; 19,0% c 5,6%. A diferença cm relação aos títulos de anticorpos detectados através de HAI, RIFI, RFC e CIEP e em relação à presença de trofozoitas ou cistos nas fezes foi significativa para as quatro reações imunológicas, quando X² foi empregado (P < 0,05).
Anticorpos anti-Entamoeba histolylica em indivíduos com amebíase intestinal apresentando cistos e/ou trofozoitas nas fezes
Keywords: Entamoeba histolytica; IHA; IFAT; CFR; CIEP; cysts; trophozoites